Valorization of secondary copper slag as aggregate and cement replacement in ultra-high performance concrete. (15th August 2022) - Edwin, Romy Suryaningrat; Gruyaert, Elke; De Belie, Nele
Abstract: This study aims to examine the influence of quickly cooled granulated copper slag (QCS) and finely ground slowly cooled broken copper slag (SCS) as basalt aggregate and cement replacement, respectively, in ultra-high performance concrete (UHPC). The UHPC mixtures and cement pastes having a water-to-binder ratio of 0.18 were produced with different proportions of QCS-aggregate (up to 60% aggregate replacement) and SCS-binder (up to 20% cement replacement) and intensive vacuum mixing and heat curing were applied to the mixtures. The pozzolanic activity of SCS-binder was determined by bound water test. The evolution of the UHPC porosity was investigated by mercury intrusion porosimetry. A leaching test was performed on concrete containing copper slag to monitor the heavy metals release. The results obtained, revealed that the mechanical strength of UHPC containing QCS-aggregate and SCS-binder were comparable to or even better than for the reference mixture. The use of vacuum mixing combined with heat curing had a limited effect on strength and porosity reduction of concrete. The chemically bound water of cement pastes decreased as the SCS-binder content increased, indicating low pozzolanic activity of the SCS-binder used in this study. However, the relative contribution of SCS-binder increased with time, as the pozzolanic reaction of this SCS-binder continues for the longer curing ages. The UHPC made with copper slag meets the specific technical and health and safety requirements as construction material since the leachability results were below the Toxicity Characteristic Leaching Procedure limit values. Highlights: The use of copper slag-aggregate had no significant effect on concrete strength. The effect of the vacuum technique to increase the strength of concrete is limited. No detrimental effect on the strength of concrete containing copper slag-binder. The leachability results of concrete with copper slag were below the limit values.